Rehospitalizations Following Primary Percutaneous Coronary Intervention in Patients With ST‐Elevation Myocardial Infarction: Results From a Multi‐Center Randomized Trial. Issue 8 (August 2017) - Spitzer, Ernest; Frei, Martina; Zaugg, Serge; Hadorn, Susanne; Kelbaek, Henning; Ostojic, Miodrag; Baumbach, Andreas; Tüller, David; Roffi, Marco; Engstrom, Thomas; Pedrazzini, Giovanni; Vukcevic, Vladan; et al.
Abstract : Background: Rehospitalizations (RHs) after ST‐elevation myocardial infarction carry a high economic burden and may deteriorate quality of life. Characterizing patients at higher risk may allow the design of preventive measures. We studied the frequency, reasons, and predictors for unplanned cardiac and noncardiac RHs in ST‐elevation myocardial infarction patients undergoing primary percutaneous coronary intervention. Methods and Results: In this post‐hoc analysis of the COMFORTABLE AMI (Comparison of Biolimus Eluted From an Erodible Stent Coating With Bare Metal Stents in Acute ST‐Elevation Myocardial Infarction; NCT00962416) trial including 1137 patients, unplanned cardiac and noncardiac RHs occurred in 133 (11.7%) and in 79 patients (6.9%), respectively, at 1 year. The most frequent reasons for unplanned cardiac RHs were recurrent chest pain without evidence of ischemia (20.4%), recurrent chest pain with ischemia and coronary intervention (16.9%), and ischemic events (16.9%). Unplanned noncardiac RHs occurred most frequently attributed to bleeding (24.5%), infections (14.3%), and cancer (9.1%). On multivariate analysis, left ventricular ejection fraction (22% increase in the rate of RHs per 10% decrease; P =0.03) and angiographic myocardial infarction Syntax score (34% increase per 10‐point increase; P =0.01) were independent predictors of unplanned cardiac RHs. Age emerged as the only independent predictor of unplanned noncardiac RHs. Regional differences for unplanned cardiac RHs were observed. Conclusions: Among ST‐elevation myocardial infarction patients undergoing primary percutaneous coronary intervention in the setting of a randomized, clinical trial, unplanned cardiac RHs occurred in 12% with recurrent chest pain being the foremost reason. Unplanned noncardiac RHs occurred in 7% with bleeding as the leading cause. Left ventricular ejection fraction and Syntax score were independent predictors of unplanned cardiac RHs and identified patient subgroups in need for improved secondary prevention. Clinical Trial Registration: URL:http://www.clinicaltrials.gov . Unique identifier: NCT00962416.